PEACEMAKERS Project: “Peace dialogue campus network: fostering positive attitudes between migrants and youth in hosting societies”: strategy paper - Koç University (2021)
Peacemakers Project team members: Koç University: Project Coordinator: Nilüfer Akpınar Şahin, Scientific Coordinator: Şebnem Köşer Akçapar, Project Assistant: Bora Berke Şahin; Universidade Aberta: Mário José Filipe da Silva, Lúcio Sousa, Rosa Maria Sequeira, Joaquim Gronita, Natália Ramos; University of Bologna: Monica Rubini, Prof. Silvia Moscatelli, Michela Menegatti, Elisabetta Crocetti, Francesca Prati, Flavia Albarello; Erasmus University Rotterdam: Phyllis Livaha; Gaziantep University: Metin Bedir, Ins. Simge Akbaş; Humboldt Universitat zu Berlin: Matthes, Kristin Küter.